Unexpected pleasures - Wine, Mary (Brava/Kensington Publishing Corp., 2012)
Forced by her guardian to tempt secrets from his enemies and seduce allegiance from his friends, Lady Justina Wincott, who will do anything to protect her son, refuses to sully the reputation of Sir Synclair, who wants to make her his wife.